Comparative study on the cultural and pathogenic variability in Alternaria brassicae (Berk.) Sacc. isolates of rapeseed-mustard - MAHESH SINGH, D. KUMAR, SUNITA SINGH, R.B. SINGH; B. SHAINY PRIYANKA, H.K. SINGH*, JAY KUMAR YADAV (Indian Phytopathology, 2016)
The fungal colonies of different isolates of Alternaria brassicae (Berk.) Sacc. varied in their cultural behavior. Cultures were found fluffy to compressed, with wavy, smooth to rough margins. Colonies colour varied from black, brown, light brown to dark brown and growth was either slow, medium or fast on different culture media. Among the media in general, the maximum growth of each fungal isolates were recorded on PDA as compare to others; while slowest growth was recorded on radish root agar medium. The maximum mycelial growth of 89.93 mm was recorded in the isolate obtained from PNUK on PDA while, minimum growth (32.40 mm) was noted on radish root agar medium of JBMP isolate. All the isolates were found pathogenic on different Brassica spp. Average maximum per cent disease intensity of isolates was recorded on B. campestris var. yellow sarson (69.70) followed by B. juncea (61.90) and was B. nigra (57.33), while it was minimum in B. carinata (18.33) and B. napus (16.50). The conidial length, width, beak length, transverse and longitudinal septation ranged between 102.68 to 141.50nm; 11.10 to 15.80nm, 49.50 to 67.55nm, 6.25 to 9.25nm, 0.75 to 1.75nm in different isolates. The maximum conidial length, width, beak length, transverse and longitudinal septation was recorded in PNUK isolate and minimum in RPCH. Isolates obtained from PNUK showed highly virulent reaction on B. campestris, isolate RPCH were less virulent. None was recorded avirulent.